Total aortic arch replacement using the thoraflex hybrid prosthesis: early- and medium-term results from a Scandinavian center. (1st October 2021) - Soknes, Maria D.; Lingaas, Per S.; Lundblad, Runar; Kvitting, John-Peder Escobar
Abstract: Objective. The purpose of this study was to assess our early experience with the Thoraflex hybrid prosthesis. Design . This was a retrospective, single-center cohort study. Results. Between December 2014 and December 2019, 34 patients underwent total aortic arch replacement with the Thoraflex hybrid prosthesis. Fifteen of the patients had pre-operative chronic aortic dissection. The mean cardiopulmonary bypass time was 200 ± 35 min, aortic cross clamp time 114 ± 34 min, deep circulatory arrest time to the lower body 60 ± 22 min, and selective antegrade cerebral perfusion time 67 ± 24 min. The rate of stroke was 11.7% (4/34), paraparesis was 8.8% (3/34) and renal failure was 11.7% (4/34). No patient required permanent dialysis. Three (8.8%) patients died within the first 30 days postoperatively. All early deaths were due to stroke or spinal cord complications. During follow-up, an additional four patients died. Average follow-up was 32.4 ± 19.4 months (1102 patient-months) and was 100% complete. Survival at 12 months and 36 months was 88% ± 7.2% and 75% ± 12.7%, respectively. Conclusions. The Thoraflex hybrid prosthesis can be used in the setting of total aortic arch replacement with good early- and medium-term results. Stroke and spinal cord complications remain an important source of early mortality.